Понятие и историческое развитие концепции правового государства и гражданского общества - Турлаев, А.В.; Хумгаев, А.Н. (Изд-во КарГУ, 2010)
Мақалада құқықтық мемлекеттің түсінігі мен тарихи даму тұжырымдамасы қарастырылады. Қазақстан Республикасындағы азаматтық қоғам мен құқықтық мемлекеттің қазіргі дамуындағы тұжырымдамалардың мəні анықталады. Азаматтық қоғам мен құқықтық мемлекеттің өзара байланыстары, негізгі белгілері жəне мақсаты мен міндеттері мазмұны ашылады. In article are considered notion and history development to concepts legal state. It Is Defined value to concepts for modern development legal state and civil society in Republic Kazakhstan. Open the main signs and relationship civil society and legal state, is defined their purpose and problems. Is achieved the survey of the scientific sources, dedicated to the stages of formation and development of civil institutes in the context of the sociopolitical development of Kazakhstan society.